Improved Pain Relief With Burst Spinal Cord Stimulation for Two Weeks in Patients Using Tonic Stimulation: Results From a Small Clinical Study. Issue 5 (16th April 2015) - Courtney, Peter; Espinet, Anthony; Mitchell, Bruce; Russo, Marc; Muir, Andrew; Verrills, Paul; Davis, Kristina
<x xml:space="preserve">Abstract</x> Objectives Conventional spinal cord stimulation (SCS) delivers a tonic waveform with consistent stream of pulses; burst delivers groups of pulses separated by short pulse‐free periods. The current study compared the short‐term safety and efficacy of burst with tonic stimulation in subjects already receiving SCS. Materials and Methods At 4 IRB‐approved sites, 22 subjects previously implanted with an SCS device for intractable, chronic pain gave informed consent and received burst stimulation for 14 days. Subjects reported average daily Visual Analog Scale (VAS) for overall, trunk, and limb pain using tonic stimulation and after 7 and 14 days of burst stimulation. Thoughts about pain were assessed using the Pain Catastrophizing Scale. Areas of paresthesia were assessed during tonic and burst stimulation using body maps. Assessment of patient satisfaction and preferred stimulation occurred after 14 days of burst. Results Average daily overall VAS reduced 46% from a mean of 53.5 (±20.2) mm during tonic SCS to 28.5 (±18.1) mm during burst (p < 0.001); trunk and limb VAS scores were also reduced by 33% and 51%, respectively. During burst, 16 subjects (73%) reported no paresthesia, 5 (23%) reported a reduction, and 1 (4%) reported increased paresthesia. After 14 days, 21 subjects (95%) reported being very satisfied or satisfied with burst. Burst was preferred by 20 subjects (91%), tonic by 1 (5%), and 1 (5%) reported no preference. Better pain relief was the most common reason cited for preference. Conclusions A majority of subjects reported improved pain relief using burst compared with tonic stimulation. Most subjects experienced less paresthesia during burst and preferred burst citing better pain relief.